Integrin-Mediated Cell-Matrix Interaction in Physiological and Pathological Blood Vessel Formation. (18th September 2011) - Niland, Stephan; Eble, Johannes A.
Abstract : Physiological as well as pathological blood vessel formation are fundamentally dependent on cell-matrix interaction. Integrins, a family of major cell adhesion receptors, play a pivotal role in development, maintenance, and remodeling of the vasculature. Cell migration, invasion, and remodeling of the extracellular matrix (ECM) are integrin-regulated processes, and the expression of certain integrins also correlates with tumor progression. Recent advances in the understanding of how integrins are involved in the regulation of blood vessel formation and remodeling during tumor progression are highlighted. The increasing knowledge of integrin function at the molecular level, together with the growing repertoire of integrin inhibitors which allow their selective pharmacological manipulation, makes integrins suited as potential diagnostic markers and therapeutic targets.